RANCANG BANGUN SISTEM INFORMASI PEMBUATAN SURAT KETERANGAN KERJA (PAKLARING) BERBASIS WEB PADA PT MAHAKARYA PUTRA MANDIRI - Ofah Musyarrofah; Mega Lestari (Journal of Innovation And Future Technology (IFTECH), 2021)
Development of the information system for making a certificate of work (paklaring) at PT. MPM is motivated by the process of making SKK, which still has many obstacles in the manufacturing process, especially in the disposition or signature of letters. Where the letter requires a signature from the leadership, but the absence of the leadership in the office often takes a relatively long time so that there are delays and delays in receiving the letter to employees who need it. This research to build an information system for making work certificates in order to facilitate the process of submitting in the disposition of letters or signatures of leaders, to be more effective and fast in the process of making SKK, The tools used are PHP and MySQL as the database. The development method used is the System Development Life Cycle (SDLC) or Waterfall. The result of this research is the application for making a work certificate.